Integration of Public Assistance Programs with Healthcare Systems: Enhancing Holistic Support for Beneficiaries - Sri Rama Satya Prasanth Vuppuluri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores integrating public assistance programs with healthcare systems, focusing on their crucial role in supporting low-income individuals and families. The article examines integration efforts' benefits, implementation strategies, challenges, and future directions. Through extensive research and data analysis, the article demonstrates how integrated systems improve health outcomes, enhance operational efficiency, generate cost savings, and elevate user experiences. The article highlights successful implementation strategies, including collaborative partnerships, integrated data systems, coordinated service delivery, and supportive policy frameworks. While acknowledging significant challenges in data security, interoperability, funding, and stakeholder engagement, the article presents evidence-based solutions and emerging technological innovations that promise to reshape the future of integrated healthcare and public assistance delivery.
Keywords: Healthcare Integration; Public Assistance Programs; Digital Health Innovation; Care Coordination; Health Information Technology